El estanque del mirlo - Speare, Elizabeth George; Millet, Ana Cristina Werring; Angelo, Nicholas (Barcelona : Noguer y Caralt, 1997)
In 1687 in Connecticut, Kit Tyler, feeling out of place in the Puritan household of her aunt, befriends an old woman considered a witch by the community and suddenly finds herself standing trial for witchcraft.
"Medalla Newbery."
Translation of: The witch of Blackbird Pond.
Keywords: Puritans -- Juvenile fiction; Prejudices -- Juvenile fiction; Paranormal fiction; Fiction